2016
DOI: 10.1007/s11239-016-1410-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulant use and the incidence of bleeding in the very elderly with atrial fibrillation

Abstract: Atrial fibrillation (AF) is a major risk factor for stroke in the elderly population. The use of anticoagulation in patients with AF greatly reduces the risk for stroke, but results in an increased risk of bleeding. Over the past several years, direct oral anticoagulants (DOACs, dabigatran, rivaroxaban, and apixaban) have been used in place of warfarin for stroke prevention in AF. We conducted a retrospective cohort study to assess the safety of DOACs in very elderly patients (75+) managed in a health care sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…However, this was not limited to rivaroxaban, but also to the other DOACs as will be discussed in subsequent sections. Indeed, in a study with 140 elderly patients taking DOACs, 21 patients (15%) were on an ILD of rivaroxaban (7 patients with 10‐mg dose and 14 patients with 15‐mg dose) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this was not limited to rivaroxaban, but also to the other DOACs as will be discussed in subsequent sections. Indeed, in a study with 140 elderly patients taking DOACs, 21 patients (15%) were on an ILD of rivaroxaban (7 patients with 10‐mg dose and 14 patients with 15‐mg dose) …”
Section: Resultsmentioning
confidence: 99%
“…Renal function dose adjustment has already proven to be a focal point. In a real‐world study with 142 patients, all the 5 observed major bleeding episodes were associated with a decline in renal function compared to baseline . Andreu Cayuelas et al also suggest that improvement in monitoring of kidney function in those undergoing therapy with DOAC would be expected to reduce risk for major haemorrhage while also protecting patients from excessive risk for thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study (n=142) assessed the safety of NOACs in elderly patients (age ≥75) [14]. Over a mean of 2.6 years, the incidence of major bleeding was low (1.37 per 100 person years) and this complication was associated with a decline in estimated creatinine clearance (eCrCl) compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, extrapolating data from clinical trials to such patients requires a degree of caution. Studies report that the lower doses of DOACs are frequently instituted without fulfilling the recommended dose‐reduction criteria (Barra et al , ; Khan et al , ) and there is a valid concern of ‘under‐dosing’. Of note also, is the small proportion of patients in ARISTOTLE who received the lower dose of apixaban – just 4·7% (Granger et al , ).…”
Section: A Tyranny Of Choice – Current Challengesmentioning
confidence: 99%